Mandatory arbitration clause vs consumer class action: Circumvention of consumer’s access to justice in Indonesia - Annisa Syaufika Yustisia Ridwan (Universitas Ahmad Dahlan, 2026)
Introduction to the problem: The emergence of the mandatory arbitration clause in consumer contracts raises the issue of consumer access to justice, for it prevents consumers from filing claims in general court. This practice might potentially close the opportunity for consumers to file a class action claim. Purpose/Study Objectives: This article aims to analyse how the mandatory arbitration clause threatens consumer access to justice, especially the future opportunity to file a class action. Since the Constitutional Court decision favoured freedom of contract and arbitration clauses, this article will attempt to find the possible approach to protect consumers amidst the practice of mandatory arbitration clauses. Design/Methodology/Approach: This paper uses a normative approach, and the data used in this paper are secondary data that consist of legal materials such as statutes, regulations, case law and doctrines. Findings: Mandatory arbitration clause poses threat to consumer access to justice. It limits the procedural right of the consumer to file a class action claim in a general court, while the current arbitration system chosen by the corporation in the clauses has a huge barrier for the consumer to access. The possible approaches to protect consumers are by challenging the validity of arbitration agreements through the undue influence doctrine and by establishing a more consumer-friendly arbitration body. Paper Type: Research Article